An Agricultural and Finance Intervention Improved Dietary Intake and Nutritional Status of Children Living in HIV-affected Households in Western Kenya (P10-129-19). (13th June 2019) - Bhandari, Shiva; Butler, Lisa; Otieno, Phelgona; Weiser, Sheri; Cohen, Craig; Frongillo, Edward
Abstract: Objectives: To test whether an intervention that was shown previously to have improved food security, dietary intake of adults, and HIV health outcomes also improved dietary intake and nutritional status of children living in HIV-affected households. Methods: The study was conducted in the Nyanza Region, Kenya where two health facilities were randomly assigned as intervention or control arms. The intervention included a human-powered water pump, a microfinance loan to purchase farm commodities, and training in sustainable farming practices and financial management. One hundred children (6 to 60 months of age) were enrolled in each arm from households with HIV-infected adults 18 to 49 years old on antiretroviral therapy and with access to surface water and land. Children were assessed beginning in April 2012 and every three months for one year. Data were collected on dietary intake, height, weight, and mid-upper arm circumference (MUAC). The difference in differences from first visit and in linear trends over visits were tested using fixed-effects regression models. Results: Compared to the control arm, children in the intervention arm had a larger increase in weight at the 12-month visit (β: 0.42, 95% CI: 0.08, 0.76) and increase in MUAC at the 6-month visit (β: 0.28, 95% CI: 0.08, 0.49), with no difference in changes in height over time. Compared to the control arm, the intervention arm had a larger increasing linear trend over time in intake of staples (β: 0.22, 95% CI: 0.02, 0.44), fruits and vegetables (β: 0.42, 95% CI: 0.10, 0.75), and meat (β: 0.07, 95% CI: 0.03, 0.12), and a larger decreasing linear trend in intake of condiments (β: -0.16, 95% CI: -0.23, -0.09) and tea (β: -0.12, 95% CI: -0.19, -0.05), with no differences in intake of eggs, dairy and fat over time. Conclusions: This intervention that improved food security, dietary intake, and HIV health outcomes of HIV-infected adults also improved dietary intake and nutritional status of children living in those households. Multisectoral agricultural and financial interventions have the potential to improve the nutritional status of HIV-affected children in rural Kenya and should be further explored. Funding Sources: National Institute of Mental Health.